Senescence and Stress Signaling Pathways in Corneal Cells After Nitrogen Mustard Injury - Khandaker N. Anwar; Mohammad Soleimani; Mohammad Javad Ashraf; Amirhossein Moghtader; Raghuram Koganti; Seyyedehfatemeh Ghalibafan; Mahbod Baharnoori; Zohreh Arabpour; Kasra Cheraqpour; Aron M. Sebhat; Mansour Abtahi; Xincheng Yao; et al. (Cells, 2024)
Mustard gas keratopathy (MGK), a complication of exposure to sulfur mustard, is a blinding ocular surface disease involving key cellular pathways, including apoptosis, oxidative stress, and inflammation. Recent studies indicate that cellular senescence contributes to the pathophysiology of mustard gas toxicity. This study aimed to assess senescence and stress-related pathways—particularly mitogen-activated protein kinase (MAPK) signaling—in nitrogen mustard (NM)-induced corneal injury. In vitro, primary human corneal epithelial (P-HCECs), primary human corneal mesenchymal stromal cells (hcMSCs), and human corneal–limbal epithelial cell (HCLE) lines were exposed to varying concentrations of NM. The results demonstrated a dose-dependent increase in cellular senescence, characterized by reduced Ki67 expression, elevated p16, and p21 mRNA levels, as well as activation of the MAPK pathway activation. Treatment with a selective p38-MAPK inhibitor significantly reduced senescence markers and improved cell proliferation following exposure to NM. Overall, these studies indicate that NM exposure triggers cellular senescence and stress-related MAPK signaling, while p38-MAPK inhibition mitigates these effects, suggesting a potential therapeutic strategy.